Electrical Control in Neurons by the Ketogenic Diet - Sada, Nagisa; Inoue, Tsuyoshi (Frontiers in Cellular Neuroscience, 2018)
The ketogenic diet is used as a diet treatment for drug-resistant epilepsy, but there are no antiepileptic drugs based on the ketogenic diet. The ketogenic diet changes energy metabolites (ketone bodies, glucose, and lactate) in the brain, which consequently changes electrical activities in neurons and ultimately suppresses seizures in epileptic patients. In order to elucidate the antiseizure effects of the ketogenic diet, it is important to clarify the mechanism by which these metabolic changes are converted to electrical changes in neurons. In this review, we summarize electrophysiological studies focusing on electrical control in neurons by the ketogenic diet. Recent studies have identified electrical regulators driven by the ketogenic diet: ion channels (ATP-sensitive K+ channels and voltage-dependent Ca2+ channels), synaptic receptors (AMPA-type glutamate receptors and adenosine A1 receptors), neurotransmitter transporters (vesicular glutamate transporters), and others (BCL-2-associated agonist of cell death and lactate dehydrogenase). Thus, the ketogenic diet presumably elicits neuronal inhibition via the combined actions of these molecules. From the viewpoint of drug development, these molecules are valuable as targets for the development of new antiepileptic drugs. Drug therapy to mimic the ketogenic diet may be feasible in the future, through the combination of multiple antiepileptic drugs targeting these molecules.